Winning matches in Grand Slam men's singles: An analysis of player performance-related variables from 1991 to 2008 - Ma, S.-M.; Liu, C.-C.; Tan, Y.; Ma, S.-C. (Journal of Sports Sciences, 2013)
This study examines factors that lead to winning matches in men's singles Grand Slam tennis, and proposes guidelines for coaches and professional tennis players both in training and preparation for Grand Slam competitions. Using longitudinal data between 1991 and 2008 retrieved from the official website of the Association of Tennis Professionals, we analysed player performance over 9,144 matches in men's singles Grand Slam tournaments. To predict match outcome, 16 variables were classified into one of three categories: player skills and performance, player characteristics and match characteristics. The three categories were entered sequentially into a logistic regression model to predict the dependent variable: the chance of winning a men's singles Grand Slam match. The final altered model explains 79.4% of the variance (Nagelkerke's pseudo R 2) in match outcomes and correctly predicted 90.6% of cases. The importance of serving, receiving, and break points is further confirmed. The positive effect of stature diminishes when players are taller than 186 cm. We recommend more training in returning skills; to avoid overestimation of the positive impact of stature, left hand and professional experience; and that a male player begins his professional tennis career by participating in the US Open or Wimbledon.